The match - Coben, Harlan, 1962- (New York : Grand Central Publishing Large Print, 2022)
When a DNA match on an online ancestry database leads him to a second cousin who disappears as quickly as he resurfaces after an epic fall from grace, Wilde must figure out if his cousin is linked to a cunning conspiracy involving a ruthless killer.
"From the creator of the Netflix drama "Stay close"--Cover.
Keywords: Abandoned children -- Fiction; Recluses -- Fiction; Fathers and sons -- Fiction; Missing persons -- Investigation -- Fiction; Fugitives from justice -- Fiction; Cousins -- Fiction; Genetic genealogy -- Fiction; Family secrets -- Fiction; Conspiracies -- Fiction; Large type books; Thrillers (Fiction); Detective and mystery fiction